Plan de gestión de riesgos en la industria metálicas Cotopaxi (I.M.C) ubicado en la parroquia San Buenaventura sector San Silvestre durante el período 2012-2013 - Quilumba Muilema, Byron Santiago (2014)
This research work was carried out at the factory Cotopaxi Metallic Industry (I.M.C) Company dedicated to the manufacture and marketing of metal joinery pressed panels, commercial kitchens and industrial bakery equipment. The company doesn’t currently have a plan for prevention of occupational risks that health care workers and comply with legal requirements and the existing legislation on Occupational Health and Safety. The study began with an analysis of the company in terms of prevention and risk identification of the same jobs that served to highlight all the flaws and served as a basis to develop the proposed Stride risks Plan. The application of this Stride risks Plan will allow that the company improves the image that have of the public opinion regarding this type of companies, and the workers enjoy a healthy work climate.